(untitled) (Ex Chordis, 2024)
The analysis of historical sources and the study of the social context provide clues to both formal solutions like the structure of a piece, and also to the philosophical attitude of the time. This article aims to suggest an interpretation of formal elements found in the Passacaglia for solo violin from the Rosary Sonatas by Heinrich Ignaz Franz Biber, in conjunction with the ‘carnal‘ physicality of the experience suggested by the Jesuit philosophy of 17th-century Salzburg. An intellectual awareness on one hand (analytical thinking) will therefore be flanked by an emotional/experiential awareness on the other (analogical thinking). In particular, the value of the number 10 within Biber‘s piece will be analysed, highlighting the structural and experiential logic of the compositional structure of the Passacaglia. The numerological approach intends to explain the structure of the piece and to be a stimulus to arrive at a performance that is more aware of historical processes, of the spatial/temporal journey experienced during the performance, and the communicative impact inherent in a rhetorically-informed performance. This article aims to invite the reader to consider similar methodologies to baroque music in general.